Common Cervicovaginal Microbial Supernatants Alter Cervical Epithelial Function: Mechanisms by Which Lactobacillus crispatus Contributes to Cervical Health - Anton, Lauren; Sierra, Luz-Jeannette; DeVine, Ann; Barila, Guillermo; Heiser, Laura; Brown, Amy G.; Elovitz, Michal A. (Frontiers in Microbiology, 2018)
The cervicovaginal (CV) microbiota is associated with vaginal health and disease in non-pregnant women. Recent studies in pregnant women suggest that specific CV microbes are associated with preterm birth (PTB). Despite demonstrating associations between the CV microbiota and adverse outcomes, the mechanisms regulating this association remain unclear. As the CV space contains an epithelial barrier, we postulate that CV microbiota can alter epithelial barrier function. We investigated the biological, molecular and epigenetic effects of L. crispatus, L. iners and G. vaginalis on cervical epithelial function and determined whether L. crispatus mitigates lipopolysaccharide (LPS) and G. vaginalis effects on the cervical epithelial barrier as a possible mechanism by which CV microbiota mitigate disease risk. Ectocervical (Ecto) and endocervical (Endo) cells treated with L. crispatus, L. iners and G. vaginalis bacteria-free supernatants alone or combined were used to measure cell permeability, adherens junction protein, inflammatory mediators and miRNAs. Ecto and Endo permeability increased after L. iners and G. vaginalis exposure. Soluble epithelial cadherin increased after L. iners exposure but not G. vaginalis or L. crispatus. A Luminex cytokine/chemokine panel revealed increased pro-inflammatory mediators in all three bacteria-free supernatants with L. iners and G. vaginalis having more diverse inflammatory effects. L. iners and G. vaginalis altered the expression of cervical, microbial and inflammatory-associated miRNAs. L. crispatus mitigated the LPS or G. vaginalis-induced disruption of the cervical epithelial barrier and reversed the G. vaginalis-mediated increase in miRNA expression. G. vaginalis colonization of the CV space of a pregnant C57/B6 mouse resulted in 100% PTB. These findings demonstrate that L. iners and G. vaginalis alter the cervical epithelial barrier by regulating adherens junction protein, cervical immune responses and miRNA expression. These results provide evidence that L. crispatus confers protection to the cervical epithelial barrier through mitigation of LPS or G. vaginalis-induced miRNAs associated with cervical remodeling, inflammation and PTB. This study provides further evidence that the CV microbiota plays a role in cervical function by altering the cervical epithelial barrier and initiating PTB. Thus, targeting the CV microbiota and/or its effects on the cervical epithelium may be a potential therapeutic strategy to prevent PTB.